EXTH-09. FIRST-IN-HUMAN DOSING CONSIDERATIONS OF A BISPECIFIC ANTIBODY FOR TREATING GLIOBLASTOMA. (11th November 2019) - Schaller, Teilo; Foster, Matthew; Spasojevic, Ivan; Gedeon, Patrick; Sanchez-Perez, Luis; Sampson, John
Abstract: Current therapy for glioblastoma (GBM) is incapacitating and limited by non-specific toxicity to the surrounding brain. We have developed an immunotherapeutic approach that selectively targets GBM by redirecting the patients' own T cells towards the tumor in an antigen-specific manner using a bispecific antibody. Our novel bispecific antibody ("BRITE") binds GBM-specific surface marker EGFRvIII and the CD3 receptor on T cells, resulting in crosslinking and tumor-specific cell lysis. We previously showed in patient-derived and syngeneic murine glioma models, that treatment with BRITE leads to long-term survival in mice with glioblastoma. A pharmacokinetic analysis in a CD3 humanized mouse revealed that BRITE in plasma and whole blood has an initial half-life of ~8 minutes and a terminal half-life of ~2.5 hours. Given our preclinical success, we have initiated clinical trial-enabling studies, including studies of BRITE toxicology and GMP manufacturing of drug product. A crucial consideration for our proposed Phase 1 dose escalation trial is the starting dose in humans. To this end, we utilized the FDA-recommended minimum anticipated biological effect level (MABEL) of BRITE – a holistic approach that considers all available in vitro and in vivo data – to calculate the first-in-human starting dose of BRITE.